2021
DOI: 10.1073/pnas.2010528118
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasmin-mediated proteolysis of L1CAM in a mouse model of idiopathic normal pressure hydrocephalus

Abstract: Idiopathic normal pressure hydrocephalus (iNPH) is a common neurological disorder that is characterized by enlarged cerebral ventricles, gait difficulty, incontinence, and dementia. iNPH usually develops after the sixth decade of life in previously asymptomatic individuals. We recently reported that loss-of-function deletions in CWH43 lead to the development of iNPH in a subgroup of patients, but how this occurs is poorly understood. Here, we show that deletions in CWH43 decrease expression of the cell adhesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Neural cell adhesion molecule L1 (L1CAM) plays an essential role in neural development, regulating processes such as neurite growth, cell migration, neuronal survival, and synaptic plasticity [ 56 ]. In humans, L1CAM mutations may cause severe neurodevelopmental defects [ 57 ]. DCC is expressed on axons and growth spines, and is also the cell surface receptor for Netrin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Neural cell adhesion molecule L1 (L1CAM) plays an essential role in neural development, regulating processes such as neurite growth, cell migration, neuronal survival, and synaptic plasticity [ 56 ]. In humans, L1CAM mutations may cause severe neurodevelopmental defects [ 57 ]. DCC is expressed on axons and growth spines, and is also the cell surface receptor for Netrin-1.…”
Section: Discussionmentioning
confidence: 99%
“…However, Yang et al [ 44 ] have now identified loss-of-function mutations in the gene CWH43 in 15% of iNPH patients. Yang et al [ 124 ] examined the mechanisms involved and found CWH43 deletions cause downregulation in the cell adhesion molecule L1CAM selectively in the ventricular and subventricular zones. It is known that mutations in L1CAM are a cause of X-linked congenital hydrocephalus [ 125 ].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Plasmin regulates fibrinolysis, the activation of growth factors, activation of MMPs, ECM degradation, hormone processing, and activation of factor V, factor VIII, factor X, and protease-activated receptors (PARs). Plasmin is associated with multiple cell functions, cytokine production, apoptosis, and tissue remodeling, as well as inflammation through various mechanisms ( Figure 2 ) [ 11 , 26 , 27 , 28 , 29 , 30 , 31 ]. In contrast, uPA and uPAR interact with transmembrane proteins, such as integrins, and regulate cell growth, migration, differentiation, and adhesion [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%